Estimation of Dissipative Heating Properties Above the Internal Boundary Layer in Landfalling Typhoons Using Multi-Layer Tower Observations - Zhou, Kang; Li, Qingqing; Tang, Jie (Frontiers in Earth Science, 2022)
Wind observations from a multi-level observation tower are used to estimate the dissipative heating (DH) in three landfalling typhoons. The observations reveal the presence of a stress internal boundary layer (IBL) in the typhoon circulations. The integrated DH values increase with increasing wind speed above the IBL. The integrated DH calculated with the turbulent spectra method increases more rapidly with increasing wind speed than that estimated with the theoretical method. However, the integrated DH estimated using the theoretical method is significantly smaller than that calculated with the turbulent spectra method because dissipative rates with the turbulent spectra method are much larger above the IBL.